2015
DOI: 10.2174/1874149501509010570
|View full text |Cite
|
Sign up to set email alerts
|

A New Structural Damage Identification Method Based on Wavelet Packet Energy Entropy of Impulse Response

Abstract: Excitation makes a great influence on the wavelet energy distribution of the response signal, this deficiency leads that the traditional structural damage identification method based on wavelet energy has a low precision. In order to solve this problem, a new structural damage identification method based on wavelet packet energy entropy (WPEE) of impulse response is presented in this paper. Firstly, natural excitation technique (NExT) is adopted to extract structural impulse response. Then, WPEE of the impulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…To identify the location of damage of the structure, a method based on singular spectrum entropy and impulse response was proposed by Li et al [10]. The method for damage localization and determining the degree of damage using the relative variation rate of wavelet packet energy entropy was also proposed by He et al [11]. Different from the above, this study proposes using WSSE for damage identification.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the location of damage of the structure, a method based on singular spectrum entropy and impulse response was proposed by Li et al [10]. The method for damage localization and determining the degree of damage using the relative variation rate of wavelet packet energy entropy was also proposed by He et al [11]. Different from the above, this study proposes using WSSE for damage identification.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Furthermore, the accuracy of the method is validated based on the identification of the location of damage. He et al [11] perform a finite element analysis on a pile structure, by calculating the relative variation in the distribution of wavelet packet energy entropy bearing the impulse response, and the relative variation is used as a recognition feature parameter for identifying the location of damage and degree of damage of the pile structure. However, experimental verification is not performed for the pile structure.…”
Section: Introductionmentioning
confidence: 99%
“…They emphasized that the method was sensitive to slight damage and suitable for highly nonlinear and nonstationary random response data due to the multiresolution signal analysis feature of CWT. He et al [41] presented a wavelet packet energy entropy based method for structural damage identification using impulse responses. They experimentally revealed that the proposed wavelet packet energy entropy based method was capable of identifying single and multiple damage in pile structures.…”
Section: Introductionmentioning
confidence: 99%
“…Since steel bridges su er from complex working conditions during their service life, heavy working loads and other e ects damage structures and accelerate the development of damages. With the accumulation of damages to structures, the safety of both the structure and human life can be threatened and may directly result in tragedies of life and property [1,2]. Therefore, structural damage identi cation has become an important research topic in the engineering protection eld [3].…”
Section: Introductionmentioning
confidence: 99%